Effect Of Organizational Culture And Work Environment On Employee Performance Of PT.Nafasindo Medan - A Mahendra; Ronnie Togar Mulia Sirait; Brema Oktavianta Sitepu (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of organisational culture and work environment on the employee performance of PT. Nafasindo Medan. The decline in employee performance is due to corporate culture and work environment. The population in this study was: 75 employees. The number of samples in this study was 75 employees. The sampling technique used is total sampling. Data collection techniques are by distributing questionnaires and interviews. Data analysis uses multiple linear regression analysis. The study concludes that Organizational Culture has a positive and significant effect on the Employee Performance of PT. Nafasindo Medan. Partially, the Work Environment has a positive and significant impact on the Employee Performance of PT. Nafasindo Medan. Simultaneously Organizational Culture and Work Environment have a positive and significant effect on the Employee Performance of PT. Nafasindo Medan.